Foreign versus domestic institutional investors in emerging markets: Who contributes more to firm-specific information flow? - Jeong-Bon Kim; Cheong H. Yi (China Journal of Accounting Research, 2015)
Using a large sample of firms listed on the Korea Stock Exchange over 1998-2007, this study investigates whether and how trading by foreign and domestic institutional investors improves the extent to which firm-specific information is incorporated into stock prices, captured by stock price synchronicity. We find, first, that stock price synchronicity decreases significantly with the intensity of trading by foreign investors and domestic institutional investors. Second, trading by foreign investors facilitates the incorporation of firm-specific information into stock prices to a greater extent than trading by aggregate domestic institutions. Third, among domestic institutions with differing investment horizons, short-term investing institutions, such as securities and investment trust companies, play a more important role in incorporating firm-specific information into stock prices via their trading activities, compared with long-term investing institutions, such as banks and insurance companies. Finally, we provide evidence suggesting that trading by foreign and domestic short-term institutions reduces the extent of accrual mispricing. Our results are robust to a variety of sensitivity checks.
Keywords: 650; Foreign investors; Institutional trading; Investment horizon; Stock price synchronicity; Korea